CODE-SWITCHING IN ENGLISH CLASSROOM INTERACTION IN A JUNIOR HIGH SCHOOL - Ainy Mauliddiyah; Ahmad Munir; Ali Mustofa (Institut Pendidikan Tapanuli Selatan, 2019)
Abstract Code switching is not only encountered in social contexts, but we can also find it in the context of English classroom interaction. Therefore this study aims to observe code-switching that occurred in good English class interactions. That has been done by the students or by a teacher. This research was conducted to find out what factors that triggers the occurrence of code switching in English classroom interactions at the junior high school. The data in this study were analyzed qualitatively and through several stages, namely: such as (1) transcription of data, (2) classification of data, (3) analysis of data for the use of code that occurred in English class interactions and (4) data interpretation. Based on the results of data analysis, the results of this study indicated that the factors that trigger the occurrence of code-switching in English classroom interactions, the first factor was do not know words or sentences in English, the second factor was to avoid misunderstandings, the third was add emphasis factor on a sentence by repeating words, the fourth was a trigger factor for the participation of others (friends, other students, or teachers) Keywords: Code-Switching, Interaction in the Class, Data Transcription, Triggering Factors for Code-Switching